PENINGKATAN KEMAMPUAN BERHITUNG ANAK MELALUI PERMAINAN GOLF BUAH DI PASAMAN BARAT - Hartinah, Hartinah (Jurnal Ilmiah Pesona PAUD, 2012)
Ability calculate still lower like sort number device caused by less precise method, target of research to increase ability calculate child through game of fruit golf. Research type In form of PTK, subjek research of child of Taman Kanak-kanak Negeri Pembina, group of B2 with amount of child 20 one who consist of men 8 and woman 12 people. Research data obtained from documentation and observation processed with percentage technique. This research is conducted with two cycle. Result of research every cycle have shown the existence of the make-up of ability calculate child through game of fruit golf. Pursuant to result of action which have can be taken by conclusion that the happening of make-up of ability calculate child through game of fruit golf.